2016
DOI: 10.1007/s11095-016-1950-0
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin E Analog Gamma-Tocotrienol (GT3) Suppresses Radiation-Induced Cytogenetic Damage

Abstract: PurposeIonizing radiation (IR) generates reactive oxygen species (ROS), which cause DNA double-strand breaks (DSBs) that are responsible for cytogenetic alterations. Because antioxidants are potent ROS scavengers, we determined whether the vitamin E isoform γ-tocotrienol (GT3), a radio-protective multifunctional dietary antioxidant, can suppress IR-induced cytogenetic damage.MethodsWe measured DSB formation in irradiated primary human umbilical vein endothelial cells (HUVECs) by quantifying the formation of γ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…It was found that gamma tocotrienol modulates as many as 27 gene clusters in human umbilical vein endothelial cells involved in DNA damage (BERBEE et al, 2012). Pathak et al (2016), suggested several mechanisms to explain how gamma-tocotrienol detoxifies ROS. Gamma-tocotrienol may regulate mitochondrial activity, transcription factors, or endothelial cell surface receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that gamma tocotrienol modulates as many as 27 gene clusters in human umbilical vein endothelial cells involved in DNA damage (BERBEE et al, 2012). Pathak et al (2016), suggested several mechanisms to explain how gamma-tocotrienol detoxifies ROS. Gamma-tocotrienol may regulate mitochondrial activity, transcription factors, or endothelial cell surface receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The vitamin E isoforms tocotrienol are natural dietary antioxidant and a potent radioprotector, with the largest dose reduction factor among all the natural products (GHOSH et al 2009). Many studies do not fully understand how tocotrienol protects against radiation damage but it may regulate apoptotic signals, cytokine production, cholesterol biosynthesis, or progenitor cell mobilization (PATHAK et al, 2016). Moreover, gene-expression profiles suggest that γ-tocotrienol affects a number of genes known to be important for the DNA damage response (BERBEE et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DNA damage taking place in human white blood cells in vitro appeared to be related to consumption of dietary antioxidants [169]. Additionally, in a recent study [141], human umbilical vein endothelial cells were subjected to gamma-irradiation where gamma-tocotrienol was found to attenuate DNA double-strand breaks. Moreover, the same work showed an increase in the expression of the DNA repair RAD50, therefore highlighting the importance of gamma-tocotrienol and its sources as a potential therapeutic strategy to reduce irradiation-induced genetic diseases.…”
Section: Tocopherols and Tocotrienols In Health Promotionmentioning
confidence: 99%
“…9) In addition, PATHAK et al have demonstrated that GT3 pretreatment reduced DNA double-strand breaks formation in human umbilical vein endothelial cells (HUVECs), and also decreased chromosomal aberrations in both HUVECs and mouse bone marrow cells after irradiation. 65) Moreover, GT3 increased expression of the DNA-repair gene RAD50 and attenuated radiation-induced RAD50 suppression. Currently, GT3 is being investigated for its ef cacy against 60 Co -irradiation using a NHP model.…”
Section: Cblb502mentioning
confidence: 98%